2006
DOI: 10.1111/j.1469-8137.2005.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Baobab trees (Adansonia) in Madagascar use stored water to flush new leaves but not to support stomatal opening before the rainy season

Abstract: Summary• Baobab trees ( Adansonia , Bombacaceae) are widely thought to store water in their stems for use when water availability is low. We tested this hypothesis by assessing the role of stored water during the dry season in three baobab species in Madagascar.• In the dry season, leaves are present only during and after leaf flush. We quantified the relative contributions of stem and soil water during this period through measures of stem water content, sap flow and stomatal conductance.• Rates of sap flow at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
3
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 37 publications
6
95
3
8
Order By: Relevance
“…This rainfall is unlikely to influence soil water availability for the trees, but may facilitate leaf flushing by increasing relative humidity and reducing vapour pressure deficit Myers et al 1998). Water storage within plants may also influence phenological patterns (Borchert 1994a;Borchert and Rivera 2001;Rivera et al 2002;Chapotin et al 2006). In this study, however, water storage ability was not observed to facilitate dry season leaf flushing, with the two stem succulent species (Spondias pinnata and Tetrameles nudiflora) observed to consistently flush leaves during the early wet season.…”
Section: Timing and Patterns Of Leaf Flushingcontrasting
confidence: 45%
See 1 more Smart Citation
“…This rainfall is unlikely to influence soil water availability for the trees, but may facilitate leaf flushing by increasing relative humidity and reducing vapour pressure deficit Myers et al 1998). Water storage within plants may also influence phenological patterns (Borchert 1994a;Borchert and Rivera 2001;Rivera et al 2002;Chapotin et al 2006). In this study, however, water storage ability was not observed to facilitate dry season leaf flushing, with the two stem succulent species (Spondias pinnata and Tetrameles nudiflora) observed to consistently flush leaves during the early wet season.…”
Section: Timing and Patterns Of Leaf Flushingcontrasting
confidence: 45%
“…Nepstad et al 1994) or are capable of storing water in their stems during the dry season (e.g. Chapotin et al 2006), this correlation may be weak or nonexistent. Nonetheless, it is reasonable to expect that the internal water status of the tree, which is a function of species-specific physiology, soil-water availability, rainfall, temperature, and relative humidity, will show considerably more interannual variation than photoperiod.…”
Section: Proximate Causes Of Leaf Flushingmentioning
confidence: 99%
“…However, recent understandings are that the stem water is reserved for the fresh leaf flushing as well as to keep these leaves active for several weeks after the start of the dry season [12,6]. The stem water was also found not to play a role in maximizing stomatal conductance, which is generally lower in Jatropha than that of co-occurring species and which decreases during the day [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…It can vary among geographical locations and in response to changes in environmental factors such as soil fertility, temperature and rainfall (Muller-Landau 2004, Nogueira et al 2005, Chave et al 2006). In the Amazon basin, it is believed that wood density can give information about the successional stage of a forest on a given location , Nogueira et al 2008.…”
Section: Introductionmentioning
confidence: 99%